Pengaruh Kualitas Produk, Cita Rasa dan Word of Mouth terhadap Keputusan Pembelian pada Cake Boss di Delta Sari Indah Waru Sidoarjo - Astuti, Risa Eno; Astuti, Mudji (Indonesian Journal Publisher, 2023)
This study aims to determine the effect of product quality, taste and word of mouth on purchasing decisions at Cake Boss at Delta Sari in Waru Sidoarjo. This research is a descriptive study using quantitative methods. The data collection technique is by distributing questionnaires to 98 respondents who are consumers of Cake Boss. The analytical technique used in this research is multiple linear regression using SPSS (Statistical Program for Social Service) version 22 for windows.The results of this study indicate that product quality variables affect purchasing decisions, taste variables affect purchasing decisions, word of mouth variables affect purchasing decisions and product quality variables, taste and word of mouth influence jointly on purchasing decisions on Cake Boss.